Pharmacokinetics and testing of dosage regimen of cefazolin post intravenous injection in healthy female buffalo calves - JAYACHANDRAN, C; NIRALA, R K; AGRAWAL, A K (The Indian Journal of Animal Sciences, 2014)
Pharmacokinetics and testing of dosage regimen of cefazolin was carried out in 4 healthy female buffalo calves after its intravenous (iv) administration @ 10 mg/kg. Plasma and urine concentrations of cefazolin were estimated at various time intervals by microbiological assay using Sarcina lutea (ATCC 9341). From log plasma concentrations versus time, kinetics parameters were calculated. Based on kinetic parameters, loading (D*) and maintenance (D0) doses were calculated for maintaining CP∞ min (MIC) of 0.5 μg/ml at the dosage interval (γ) of 6 Using the data, appropriate D* was injected i/v and 3 consecutive Do were given at selected dosage interval (γ) of 6 h to maintain CP∞ min of 0.5 μg/ml in each animal. The study obtained distribution (t1/2 ß) and elimination (t1/2 β) half life, volume distribution, and total body clearance (ClB) of 0.19±0.06 h, 4.78±0.28 h, 5.49±0.83 L/ kg and 13.15±1.53 ml/kg/min. D* and D0 of 6.52±0.77 and 3.77±0.38 mg/were calculated to maintain CP∞ min of 0.5 μg/ml at γ of 6 h.